Silencing of long chain noncoding RNA paternally expressed gene (PEG10) inhibits the progression of neuroblastoma by regulating microRNA-449a (miR-449a)/ribosomal protein S2 (RPS2) axis. Issue 3 (1st March 2022) - Zhang, Jian; Liu, Wei; Ji, Ping; Zhang, Yan
ABSTRACT: To investigate the mechanism of paternally expressed gene (PEG10) in regulating neuroblastoma (NB) progression. PEG10 expression was detected using quantitative real-time reverse transcription polymerase-chain reaction (qRT-PCR). The interaction of miR-449a and PEG10 or ribosomal protein S2 (RPS2) was employed by starBase, and then proved through RIP and dual-luciferase reporter assays. The NB cell viability, proliferation, invasion, and migration were evaluated by Cell Counting Kit-8 (CCK-8), colony formation, and Transwell assay. The mRNA and protein levels were determined by qRT-PCR and Western blotting, respectively. The levels of PEG10 and RPS2 were remarkably increased in NB tissues and cells, nevertheless the expression of miR-449a was conspicuously declined in NB tissues and cells. Silencing of PEG10 inhibited proliferation, migration, and invasion in SK-N-BE (2) cells, while overexpression of PEG10 promoted proliferation, migration, and invasion in SH-SY5Y cells. We affirmed that PEG10 interacted with miR-449a, and miR-449a could target the 3ʹUTR of RPS2 and negatively regulate its expression in NB cells. The upregulation of miR-449a inhibited proliferation, migration, and invasion in SK-N-BE (2) cells, while downregulation of miR-449a promoted proliferation, migration, and invasion in SH-SY5Y cells. Moreover, miR-449a overexpression weaken the function of PEG10-mediated on promoting proliferation, migration, and invasion in SH-SY5Y cells, while RPS2 overexpression rescued the effects of miR-449a-mediated on inhibiting those behaviors of SH-SY5Y cells. In conclusion, Silencing of PEG10 could inhibit proliferation, migration, and invasion via the miR-449a/RPS2 axis in NB cells. Graphical Abstract: uf0001